(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Currently, the issue of employment of young people, especially graduates of higher educational institutions, is very acute. Today, many employers do not want to hire young specialists, since they have no work experience, and industrial practices in universities do not provide the necessary professional training.